Pulmonary fibrosis: "idiopathic" is not "cryptogenic". Issue 3 (19th March 2019) - Wells, Athol U.; Brown, Kevin K.; Flaherty, Kevin R.; Kolb, Martin; Thannickal, Victor J.
The writer makes a powerful plea for clarity of thought based on clarity of language, arguing from the Socratic maxim that "the beginning of wisdom is the definition of terms". This etymological perspective is extremely apposite because the distinction between "cryptogenic" and "idiopathic" disease is seminal in the ongoing idiopathic pulmonary fibrosis (IPF) terminology debate. The additional argument advanced by Professor Cottin for retention of the term "idiopathic pulmonary fibrosis" is highly persuasive http://ow.ly/n05630nVCZd